Implementasi Model Pembelajaran Numbered Heads Together (NHT) dalam Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran PAI di SMA - Ernasari, Resi; Sulaiman, Sulaiman (Prodi Pendidikan Keagamaan Islam, 2023)
In the learning process of Islamic Religious Education, many students are less active so it is necessary to apply the right learning model, one of which is by using the Numbered Heads Together (NHT) learning model. This study aims to determine how the application of the Numbered Heads Together (NHT) learning model can increase student learning activeness and what are the advantages and disadvantages of applying the NHT learning model in Islamic Religious Education subjects at SMA N 1 Sutera. This type of research is qualitative research with the subject of students of class XII IPA 1 at SMA N 1 Sutera totaling 36 people. Data were collected through interviews, observation and documentation. The results of this study are the implementation of the NHT learning model carried out by the teacher by giving numbers and the task for each number in the group to convey the results of the discussion according to the number called makes student activeness in PAI subjects increase. The advantage of the NHT model is that it can increase student activeness and sense of responsibility. The weakness lies in the limited time due to the large number of students.